AT1 receptor blockade in the central nucleus of the amygdala attenuates the effects of muscimol on sodium and water intake. (29th October 2015) - Hu, B.; Qiao, H.; Sun, B.; Jia, R.; Fan, Y.; Wang, N.; Lu, B.; Yan, J.Q.
Highlights: Intra-CeA losartan increased sodium intake inhibited by muscimol in WD–PR rats. Intra-CeA losartan increased sodium intake inhibited by muscimol in FURO rats. AT1 receptors are involved in the GABAergic regulation of salt intake in the CeA. Abstract: The blockade of the central nucleus of the amygdala (CeA) with the GABAA receptor agonist muscimol significantly reduces hypertonic NaCl and water intake by sodium-depleted rats. In the present study we investigated the effects of previous injection of losartan, an angiotensin II type-1 (AT1) receptor antagonist, into the CeA on 0.3 M NaCl and water intake reduced by muscimol bilaterally injected into the same areas in rats submitted to water deprivation–partial rehydration (WD–PR) and in rats treated with the diuretic furosemide (FURO). Male Sprague–Dawley rats with stainless steel cannulas bilaterally implanted into the CeA were used. Bilateral injections of muscimol (0.2 nmol/0.5 μl, n = 8 rats/group) into the CeA in WD–PR-treated rats reduced 0.3 M NaCl intake and water intake, and pre-treatment of the CeA with losartan (50 μg/0.5 μl) reversed the inhibitory effect of muscimol. The negative effect of muscimol on sodium and water intake could also be blocked by pretreatment with losartan microinjected into the CeA in rats given FURO ( n = 8 rats/group). However, bilateral injections of losartan (50 μg/0.5 μl) alone into the CeA did not affect the NaCl or water intake. These results suggest that the deactivation of CeA facilitatory mechanisms by muscimol injection into the CeA is promoted by endogenous angiotensin II acting on AT1 receptors in the CeA, which prevents rats from ingesting large amounts of hypertonic NaCl and water.